Postoperative outcomes of natural orifice transluminal endoscopic surgery-assisted vaginal hysterectomy and conventional laparoscopic-assisted vaginal hysterectomy: a comparative study - Seong Hee Kim; Chan Hee Jin; In Taek Hwang; Jun Sook Park; Jung Hwan Shin; Dae Woon Kim; Yong Soo Seo; Jee Nah Sohn; Yun Seok Yang (Korean Society of Obstetrics and Gynecology, 2018)
ObjectiveThe present study aimed to determine the differences in outcomes between natural orifice transluminal endoscopic surgery-assisted vaginal hysterectomy (NAVH) and conventional laparoscopy-assisted vaginal hysterectomy (LAVH).MethodsWe retrospectively reviewed the charts of patients who between July 2012 and September 2015, were diagnosed as having benign uterine disease such as uterine myoma, endometriosis, or adenomyosis and managed via NAVH or LAVH in a single-center (Eulji University Hospital). Data such as age, body weight, height, parity, operation time, intra/post-operative complications, and uterus weight were obtained from the clinical charts. NAVH and LAVH recipients were matched 1:3 in terms of baseline characteristics, and the 2 groups were compared regarding surgical outcomes.ResultsOf the 160 patients with benign uterine disease included in the present study. Forty received NAVH and remaining 120 received LAVH. There were significant differences between the groups regarding operation time and hemoglobin change. Notably, although the operation time was shorter for LAVH, hemoglobin change was lower for NAVH. Additionally, although maximum hospitalization duration was shorter for LAVH, the average length of hospitalization was similar between NAVH and LAVH. There were no significant differences between the groups in terms of other variables.ConclusionNAVH may become a new alternative surgical method of choice for hysterectomy, as it represents a clinically feasible and safe approach; moreover is superior to LAVH in terms of bleeding loss.